Research Trends in Digital Financial Inclusion: A Bibliometric Analysis using VOSviewer - Ahiase, Godwin; Umar, Abdurrauf; Marwan. M. Saeed, Abdulmalek; Abedin Rasuman, Mohammad; Rianti do Rego Tilman Suri, Epifania (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2024)
Digital financial inclusion (DFI) aims to provide affordable and sustainable financial services to financially excluded and underserved populations through cost-saving digital means. The purpose of the study is to conduct a bibliometric analysis of DFI using VOSviewer software. A bibliometric and descriptive quantitative approach was employed. Data was collected based on the keyword "digital financial inclusion" from Google Scholar. From the search results, 982 articles published between 2018 and 2023 were found, with 125 relevant to the topic. The number of DFI publications increased from 7 in 2018 to 18 in 2019, indicating a growing interest. The number remained stable in 2020 and 2021, but there was a significant surge in research interest in 2022 with 37 publications. This study demonstrates the relevance of bibliometric analysis, particularly in the field of DFI. The findings are essential for policymakers, researchers, and practitioners to determine the novelty and quantity of data.